1992
DOI: 10.1007/bf02051014
|View full text |Cite
|
Sign up to set email alerts
|

Malignant cells are collected on circular staplers

Abstract: Anastomotic recurrence after resection of colorectal carcinoma has been attributed to insufficient clearance, migration of tumor cells into lymphatics, or implantation of exfoliated malignant cells during anastomosis. We studied 10 patients submitting to low anterior resection for cancer 6 to 16 cm (mean, 12.6 cm) from the anal verge. The anastomosis was performed with a circular stapler introduced transanally into the rectum using the established technique. No lavage of the rectal stump with a cytotoxic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
84
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(95 citation statements)
references
References 25 publications
2
84
0
8
Order By: Relevance
“…substantial evidence exists indicating the presence of viable cancer cells in the bowel lumen of patients with colorectal cancer at the time of operation (14-16), which can be detected on suture or staple lines of anastomosis (17). Anastomotic leakage, the most frequent infectious complication found in this study, may lead to extraluminal implantation, which has the effect of upstaging the disease and increasing the incidence of locoregional relapse (13).…”
Section: Discussionmentioning
confidence: 66%
“…substantial evidence exists indicating the presence of viable cancer cells in the bowel lumen of patients with colorectal cancer at the time of operation (14-16), which can be detected on suture or staple lines of anastomosis (17). Anastomotic leakage, the most frequent infectious complication found in this study, may lead to extraluminal implantation, which has the effect of upstaging the disease and increasing the incidence of locoregional relapse (13).…”
Section: Discussionmentioning
confidence: 66%
“…Cancer cells have also been found on the doughnuts of bowel following the use of the circular stapler. 25 Rectal washout with saline has been shown to reduce the number of cancer cells within the lumen and at the site of the anastomosis. 26,27 The best results, however, come from performing the rectal washout with a hypotonic solution such as water and/or antiseptic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies have revealed that multiple clusters of malignant cells can collect on a circular stapler used to produce an anastomosis when resecting for rectal cancer [11,13,14]. Gertsch et al [13] and Jenner et al [11] reported that cytology revealed malignant cells in centrifuged saline used for washing circular staplers in nine of ten and eight of ten cases of low anterior resection, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Gertsch et al [13] and Jenner et al [11] reported that cytology revealed malignant cells in centrifuged saline used for washing circular staplers in nine of ten and eight of ten cases of low anterior resection, respectively. Such malignant cells that collect on a stapler can be trapped or implanted in the suture line when constructing an anastomosis and hence cause subsequent suture-line recurrence [11,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%